An asymmetric hydrocyanation/Michael reaction of α-diazoacetates via Cu(i)/chiral guanidine catalysis. Issue 14 (23rd January 2020) - Ruan, Sai; Zhong, Xia; Chen, Quangang; Feng, Xiaoming; Liu, Xiaohua
Abstract : An asymmetric one-pot hydrocyanation/Michael reaction of α-aryl diazoacetates with trimethylsilyl cyanide, tert -butanol, and N -phenylmaleimides has been realized using a chiral guanidinium salt/CuBr catalyst. Abstract : An asymmetric one-pot hydrocyanation/Michael reaction of α-aryl diazoacetates with trimethylsilyl cyanide, tert -butanol, and N -phenylmaleimides has been realized. Using a chiral guanidinium salt/CuBr catalyst, a series of cyanide-containing pyrrolidine-2, 5-diones could be obtained in good yields with excellent diastereo- and enantioselectivities.